1997
DOI: 10.1142/s0218810497000185
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of the Stress Force on Midcarpal Joint in Kienböck's Disease

Abstract: Two types of lunate were recognized in the midcarpal joint. Type I lunate has no facet articulation with the hamate, and Type II lunate has a facet articulation with the hamate. The purposes of this study are to estimate the biomechanical contribution of Type II lunate for Kienböck's disease, and to elucidate the change of the contact surface between the lunate and hamate during radial and ulnar deviation for both Type I and Type II. Twenty-four contralateral unaffected wrists with Kienböck's disease were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 0 publications
1
24
0
4
Order By: Relevance
“…Nakamura et al reported that the shortest distance between the capitate and triquetrum (C-T distance) was the best determinant of lunate type, and that the C-T distance increased as the actual width of the lunate ulnar facet increased. 33 Nakamura et al defined type I lunates as those having a C-T distance of Ͻ2 mm and type II lunates as those having a C-T distance of Ͼ4 mm. 20 Hamate type: The hamate was analyzed for the presence or absence of the hamate groove and distal hamate ridge on its midcarpal surface.…”
Section: Identification Of Carpal Morphological Typesmentioning
confidence: 99%
See 4 more Smart Citations
“…Nakamura et al reported that the shortest distance between the capitate and triquetrum (C-T distance) was the best determinant of lunate type, and that the C-T distance increased as the actual width of the lunate ulnar facet increased. 33 Nakamura et al defined type I lunates as those having a C-T distance of Ͻ2 mm and type II lunates as those having a C-T distance of Ͼ4 mm. 20 Hamate type: The hamate was analyzed for the presence or absence of the hamate groove and distal hamate ridge on its midcarpal surface.…”
Section: Identification Of Carpal Morphological Typesmentioning
confidence: 99%
“…23 Nakamura et al reported that the shortest distance between the capitate and triquetrum (the C-T distance), measured on plain AP radiographs or coronal CT, was the best determinant of lunate type, and that the C-T distance increased as the actual width of the ulnar facet increased. 33 Nakamura et al defined type I lunates as having a C-T distance of Ͻ2 mm and type II lunates as having a C-T distance of Ͼ4 mm. 20 In this study, the average C-T distance of type I lunates was 2.50 mm (R, 0.70 -3.65; SD, 1.05), which was higher than that reported by Nakamura et al 33 Lunates with small, cartilaginous ulnar facets had an average C-T distance of 2.68 mm (R, 2.20 -3.18; SD, 0.49).…”
Section: Lunatementioning
confidence: 99%
See 3 more Smart Citations